Vessel-source marine pollution : the law and politics of international regulation / Alan Khee-Jin Tan. - Tan, Alan Khee-Jin (Cambridge studies in international and comparative law (Cambridge, England : 1996) ;, 2006)
Analysing the regulation of vessel-source pollution from the perspective of the political interests of key players in the ship transportation industry, this 2005 book by Alan Khee-Jin Tan offers a comprehensive and convincing account of how pollution of the marine environment by ships may be better regulated and reduced. In this timely study, he traces the history of regulation at the International Maritime Organization (IMO) and investigates the political, economic and social forces influencing the IMO treaties. Also examined are the efforts of maritime states, ship-owners, cargo owners, oil companies and environmental groups to influence IMO laws and treaties. This is an important book, which uncovers the politics behind the law and offers solutions for overcoming the deficiencies in the regulatory system. It will be of great interest to professionals in the shipping industry as well as practitioners and students.